An Analysis on The English Teacher Strategies in Teaching Reading Comprehension of The Twelfth Grade Students - Wulandari, Jenny Aprillia; Wahab, Abdul Aziz; Ferdiyanto, Feri (Universitas Nurul Jadid, 2024)
The purpose of this study was to identify, analyze, and describe the teacher's strategies for teaching reading comprehension. The subject of this research is an English teacher at MA Uswatun Hasanah. The researchers conducted this research in the twelfth grade with twenty-six students. In this study, the researchers used descriptive-qualitative methods. The techniques of data collection are observation, interview, and documentation. The results of this study show that there are two English teacher strategies used in learning: scientific and drill. The results of the study showed that both English teachers’ strategies produced a positive impact on the development of students' knowledge, especially in reading comprehension. This strategy also made students enthusiastic and active during learning activities. English teachers also did not experience difficulties when implementing these learning strategies.